From zeolites to porous MOF materials–the 40th anniversary of International Zeolite Conference : proceedings of the 15th International Zeolite Conference, Beijing, P.R. China, 12-17th August 2007 /: proceedings of the 15th International Zeolite Conference, Beijing, P.R. China, 12-17th August 2007. (2007) - Unknown
No abstract available